General Mills : driving food systems change through regenerative agriculture - Rosenzweig, William B.; Stuart, Toby; Hsu, Elaine, active 2019; Pelissier, Emily; Skonberg, Christina (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2019)
In 2019, global food company General Mills (GMI) made a public commitment to advancing regenerative agriculture on one million acres of farmland by 2030. It was a risky commitment for the company to make externally because a supply chain for regeneratively-grown ingredients doesn't exist and the company doesn't own the acreage. Also, the costs and outcome are uncertain. The Natural and Organic Operating Unit is spearheading regenerative practices which sequester carbon instead of contributing to climate change. But while Annie's Mac & Cheese consumers care about regeneratively grown products, Lucky Charms and Betty Crocker consumers are less motivated by the term. Can an acquired brand drive transformation across a 150-year-old company resulting in the triple-bottom-line they believe is critical for the planet and their long-term viability?
Originally Published In Rosenzweig, W., Stuart, T., Hsu, E., Pelissier, E., & Skonberg, C. (2019). General Mills: Driving Food Systems Change through Regenerative Agriculture. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; General Mills, Inc. -- Marketing -- Case studies; Organic farming -- Marketing -- Case studies; Business logistics -- Case studies